IPTV Channel Zap Time Analysis - Dekeris, B.; Narbutaite, L. (Elektronika ir Elektrotechnika, 2010)
This article analyzes one of the IPTV service quality indicators – channels zapping time. The propose a modified method of transmission channels change and mathematical model for IPTV network proposed. The main principle of proposed method is that, when user change the channel and look at it less then 1 minutes, less quality video (MPEG-2, SDTV) from aggregated node is send to user. After 1 minutes the transmission of high quality video starts. Using the proposed model the channel zapping time was analysed depending on the network and transferred image parameters. It was found that in the case of use of a modified algorithm, rather than a multicast transmission, channel switching time can be reduced up to 1.5 s.